Ultra-Low-Noise Operation of Broadband Uncooled PHEMT Amplifier in Ultrahigh-Frequency Band - Korolev, O. M.; Shulga, V. M. (Видавничий дім «Академперіодика», 2013)
In this paper, an approach to the design of broadband HEMT LNA is proposed, based on the selection of the transistor type adequate to the operation band. By way of the L-band amplifier, the feasibility of ultra-low-noise matching of general-purpose FET is shown. Under these conditions, the noise temperature of the amplifier (Tn) is dominantly determined by the minimum noise temperature of the transistor (Tmin) i. e. Tn/Tmin£1.2. The obtained results permit predicting the possibility of broadband LNA noise reduction down to 10 K without cryogenic cooling.